2023
DOI: 10.1093/mnras/stad269
|View full text |Cite
|
Sign up to set email alerts
|

A burst storm from the repeating FRB 20200120E in an M81 globular cluster

Abstract: The repeating fast radio burst (FRB) source FRB 20200120E is exceptional because of its proximity and association with a globular cluster. Here we report 60 bursts detected with the Effelsberg telescope at 1.4 GHz. We observe large variations in the burst rate, and report the first FRB 20200120E ‘burst storm’, where the source suddenly became active and 53 bursts (fluence ≥0.04 Jy ms) occurred within only 40 minutes. We find no strict periodicity in the burst arrival times, nor any evidence for periodicity in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 80 publications
1
20
1
Order By: Relevance
“…The rate can change from less than one burst per hour to more than 100 bursts per hour, as was observed for FRB 20121102A by Li et al (2021a) in their 60 hr of observations spanning 47 days at 1.2 GHz above a 7σ threshold of 0.015 Jy ms. Gajjar et al (2018) also reported clustered arrival times in their high-frequency (4-8 GHz) study of the same source. Nimmo et al (2023) also observed this behavior from FRB 20200120E, where they detected 53 bursts within 40 minutes, almost 80 bursts per hour. Before this epoch, the observed peak rate from the source was 0.4 0.4 2.0 -+ bursts per hour in their Effelsberg observations at 1.4 GHz above a 7σ threshold of 0.05 Jy ms.…”
Section: Burst Rate Evolutionmentioning
confidence: 55%
“…The rate can change from less than one burst per hour to more than 100 bursts per hour, as was observed for FRB 20121102A by Li et al (2021a) in their 60 hr of observations spanning 47 days at 1.2 GHz above a 7σ threshold of 0.015 Jy ms. Gajjar et al (2018) also reported clustered arrival times in their high-frequency (4-8 GHz) study of the same source. Nimmo et al (2023) also observed this behavior from FRB 20200120E, where they detected 53 bursts within 40 minutes, almost 80 bursts per hour. Before this epoch, the observed peak rate from the source was 0.4 0.4 2.0 -+ bursts per hour in their Effelsberg observations at 1.4 GHz above a 7σ threshold of 0.05 Jy ms.…”
Section: Burst Rate Evolutionmentioning
confidence: 55%
“…On timescales of order seconds to hours, bursts from repeaters tend to be clustered (e.g. Gajjar et al 2018;Zhang et al 2021;Nimmo et al 2023), in a process which is often modelled as a Weibull distribution (Oppermann, Yu, & Pen 2018) Thus it should be asked: what effect does this have on the modelling? On sufficiently long timescales, FRBs will become inactive, and new repeating FRBs will be born.…”
Section: Non-poissonian Repetitionmentioning
confidence: 99%
“…We note that another interesting constraint on the DM excess of the CGM comes from the repeating FRB 20200120E, which was recently localized to a globular cluster in M81 (Kirsten et al 2022;Nimmo et al 2023). Since the sightline does not cross the M81 disk, the DM of this FRB puts a tight upper bound on the Milky Way halo DM and M81 halo DM.…”
Section: Introductionmentioning
confidence: 86%